The politics of planning culturally relevant AIDS education for African-American women. - Elaine Archie-Booker (Adult Education Research Conference, 1997)
AIDS cases are growing faster among African-American women than for any other ethnicity-gender group. Until a vaccine or cure is available, education offers the primary means to control education. In this paper, I examine a community-based AIDS education provider to determine to what extent were their programs culturally relevant for African-American women.